Analisis Tingkat Suku Bunga dan Kaitannya Terhadap Likuiditas Sebagai Kinerja Keuangan Perbankan - Utama, Ahmad Nur Budi (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2023)
This study discusses the financial performance of banks in terms of liquidity. Banking liquidity is the ability of a bank to fulfill its financial obligations, including in providing credit to its customers. A good level of liquidity is essential in maintaining the stability of the financial sector and preventing potential financial crises. This study intends to analyze the relationship between interest rates and banking liquidity. It then identifies whether the relationship is positive or negative, and how much influence interest rates have on bank liquidity. This research uses quantitative methods with case studies at PT. BTN (State Savings Bank). liquidity in this study uses a variable loan to deposit ratio (LDR) which shows that interest rates have a significant and positive effect. Then the influence between interest rates on the liquidity of PT. BTN shows that 0.89 interest rate affects the Loan to Deposit Ratio (LDR).